THE EFFECT OF FINANCIAL LITERACY AND SOCIOECONOMIC BACKGROUND ON STUDENTS' FINANCIAL EDUCATION AT SMK PAB 2 HELVETIA - Ahmad Fadlan; Suhendi Suhendi; Atika Widya (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This research investigates the effect of financial literacy and socioeconomic background on students' financial education at SMK PAB 2 Helvetia. Financial literacy is increasingly recognized as an essential skill for managing personal finances, yet many students, particularly in vocational schools, face challenges in understanding and applying key financial concepts. The study highlights the role of socioeconomic factors, such as family income and parental education, in shaping students' financial literacy. A quantitative approach was employed, with a sample of 50 students from diverse socioeconomic backgrounds. The data was collected using a structured survey that measured financial literacy across budgeting, saving, investing, and debt management. The results, analyzed using ANOVA, reveal that students from higher-income families had significantly better financial literacy scores than those from middle- or low-income families. The study suggests that targeted financial education programs are essential for improving financial literacy, particularly for students from disadvantaged backgrounds. This research emphasizes the need for inclusive and accessible financial education tailored to the varying socioeconomic contexts of students.